2021
DOI: 10.1111/jscm.12272
|View full text |Cite
|
Sign up to set email alerts
|

Mending fences in a buyer–supplier relationship: The role of justice in relationship restoration

Abstract: While the extant literature has examined causes for buyer–supplier relationship dissolution, the restoration of severed buyer–supplier relationships has been overlooked. Drawing on organizational justice theory, our research develops and tests a model of relationship restoration. We examine how the supplier's restoration tactics—acknowledgment, compensation, and operational transparency, influence the interactional, distributive, and procedural fairness perception, respectively, of the buyer, resulting in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…We found that small buyers express this effect more strongly. Mishra (2011) found that trust, cooperation and information sharing were key to building BSRs in SMEs, although the study was limited in time and scope. His literature review found no previous studies on BSR in SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We found that small buyers express this effect more strongly. Mishra (2011) found that trust, cooperation and information sharing were key to building BSRs in SMEs, although the study was limited in time and scope. His literature review found no previous studies on BSR in SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inequity theory focuses on organisational justice (Adams, 1963) and the role of fairness in organisational relationships. Justice, fairness and the resulting behaviour are closely linked as Mir et al . (2002, p. 27) state, “ Justice, in the form of rule adherence, is the antecedent to fairness perceptions, which eventually drives behaviour .” (Mir et al ., 2022, p. 27).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, relatively weaker supply chain actors have been portrayed as passive power targets dominated by more powerful power sources, and have not been examined as key decision-makers (Tao et al ., 2022). The justice literature, so far, has also failed to investigate the perceptions of suppliers (Mir et al ., 2022) or how these are impacted by dependence and power use in supply chains.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations